Dampak Akses Finansial Terhadap Peningkatan Kualitas Sumber Daya Manusia - Meisy Amelia Putri; Marta, Joan (Media Riset Ekonomi Pembangunan (MedREP), 2025)
Enrolment in higher education is one of the indicators in improving the quality of human resources, but the cost of higher education continues to increase every year. This study aims to examine the impact of financial access on improving the quality of human capital. By using the variables of formal credit, personal loans, and leasing as indicators of financial access and participation of children aged 18 years and over continuing education to higher education as an indicator of the quality of human resources. This research uses logistic regression analysis with SUSENAS 2020 data. The results show that formal credit has a higher chance of continuing education to college than personal loans and leasing. Other factors such as education of the household head, occupation of the household head, age of the household, gender of the child, birth order of the child, completeness of parents, household consumption, region of residence, and region of residence all have a significant effect on children's participation in higher education. Improving financial access and ease of policy is recommended to increase children's participation in higher education in Indonesia.